Assessing rural youth sustainable livelihood in Malaysia - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Hamzah, Azimi; Idris, Khairuddin (Universiti Putra Malaysia Press, 2018)
The study aims to assess rural youth sustainable livelihood in Malaysia. This is a quantitative study in which a total of 240 rural youths from four districts in Peninsular Malaysia were selected as respondents. Assessment of their sustainable livelihood was based on six capitals namely, human capital, social capital, natural capital, physical capital, financial capital and cultural capital. Analysis performed confirmed that human capital was the best capital possessed by the respondents, while cultural capital was the weakest. Further analysis confirmed that the factors of gender, educational achievement and occupation had significant relationships with the types of capital studied, while the factors of age, income and period of staying in the village recorded a significant relationship with the capitals studied. The discussion highlights the important findings of this study and it is hoped that they can assist concerned parties in constructing the best strategies to further improve rural youth sustainable livelihood.